2020
DOI: 10.3390/ijerph17051649
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Mental Effort for Creating Mobile Data Collection Applications

Abstract: To deal with drawbacks of paper-based data collection procedures, the QuestionSys approach empowers researchers with none or little programming knowledge to flexibly configure mobile data collection applications on demand. The mobile application approach of QuestionSys mainly pursues the goal to mitigate existing drawbacks of paper-based collection procedures in mHealth scenarios. Importantly, researchers shall be enabled to gather data in an efficient way. To evaluate the applicability of QuestionSys, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…(2019) Computers & Security Computer Science Salo and Makkonen (2018) Communications of the Association for Information Systems Information Systems Sang et al. (2017) ACM Transactions on Intelligent Systems and Technology Artificial Intelligence Schobel et al. (2020) International Journal of Environmental Research and Public Health Public, Environmental & Occu.…”
Section: Methodology Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) Computers & Security Computer Science Salo and Makkonen (2018) Communications of the Association for Information Systems Information Systems Sang et al. (2017) ACM Transactions on Intelligent Systems and Technology Artificial Intelligence Schobel et al. (2020) International Journal of Environmental Research and Public Health Public, Environmental & Occu.…”
Section: Methodology Developmentmentioning
confidence: 99%
“…(2019) ). In this respect, four types of data are distinguished ( Taylor (2017) ; Schobel et al., 2020 ) (see Table 2 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The models are executed within an engine that is capable of running on smart mobile devices [ 37 , 38 ]. A large-scale and long-running study showed the applicability of this approach [ 39 ] and measured mental effort when implementing such mobile data collection applications [ 40 ].…”
Section: Related Work In Mhealth and Psycho-oncologymentioning
confidence: 99%
“…Among these methods, field data collection is an essential means of gathering ground-truth spatial information [2]. Field data collection plays an important role in many geospatial applications, including crop yield estimation [3], hydrologic studies [4], mobile health [5], township land resources surveying [6], and so on. The methods of collecting geographic information in the field have undergone many developments.…”
Section: Introductionmentioning
confidence: 99%